2003
DOI: 10.1021/ol0343818
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Solid-Phase Synthesis of Phthalimides

Abstract: [reaction: see text] A traceless solid-phase synthesis of substituted phthalimides is proposed. The target compounds are obtained within minutes by a microwave-assisted cyclative cleavage in good yields and excellent purities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…A number of related microwaveassisted cyclative-release protocols have been reported. [223,224] Apart from traditional cross-linked polystyrene resins a number of different supports and formats have been used in microwave-assisted SPOS. These include tentagel resins, [117,213,214,225] cellulose membranes (SPOT synthesis), [226,227] cellulose beads, [228] and glass surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…A number of related microwaveassisted cyclative-release protocols have been reported. [223,224] Apart from traditional cross-linked polystyrene resins a number of different supports and formats have been used in microwave-assisted SPOS. These include tentagel resins, [117,213,214,225] cellulose membranes (SPOT synthesis), [226,227] cellulose beads, [228] and glass surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Chassaing et al have developed a traceless solid-phase synthesis of N-substituted phthalimide libraries. 132 The synthetic route involves the use of the Wang resin loaded with phthalic acid employing the Mitsunobu protocol. Subsequent reaction with alkyl or aralkyl amines under standard amide coupling conditions led to the generation of resin-bound N-alkyl or benzylphthalamic acids.…”
Section: Scheme 28mentioning
confidence: 99%
“…Kappe and Stadler have shown that PS resins tolerate microwave heating up to temperatures of 200 • C [38]. A wide variety of successful microwave-assisted transformations on PS support has been reported [37,38,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Insoluble Polymer Supportsmentioning
confidence: 99%
“…A related microwave-assisted cyclative cleavage strategy was proposed for the synthesis of substituted phthalimide libraries by Chassaing et al [60]. It should be noted that protocols using conventional heating [167,168] were found to be unfeasible for large library production, as they required reaction times of several hours.…”
Section: Phthalimide Library Synthesis On Wang Resinmentioning
confidence: 99%